The Effect of Instagram Marketing Activities on Repurchase Intention Mediated by Brand Image and Brand Trust - Nur Alpiani Kumalasari; Lia Amalia (International Journal of Economics (IJEC), 2026)
Instagram marketing activities an important role in marketing strategies that can be implemented by fast food restaurants by providing information that suits consumer needs and providing a quick response in receiving all forms of criticism so that consumer trust increases in the company and makes repeat purchases in the future. The purpose of this study was to determine how much influence Instagram marketing activities have on brand image and brand trust and repurchase intention in fast food restaurants among generation Z. This type of research is quantitative with a purposive sampling technique distributed through a questionnaire of fast food restaurant consumers aged 18-27 years and domiciled in the Bekasi area. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that the Instagram marketing activities variable has the greatest direct influence on brand trust, then the brand trust variable has the greatest indirect influence between the relationship between Instagram marketing activities and repurchase intention. This study contributes to fast food restaurants in maintaining and increasing consumer trust can be seen from several factors, namely prioritizing food quality as an effort to improve restaurant quality, especially related to the menu offered. High quality will provide greater customer satisfaction, of course it will be more in demand by generation Z. For further research, researchers plan to expand the research area and look for objects in other fields.